Etica della potenza. Percorsi spinoziani (FedOA - Federico II University Press, 2026)
What is produced when a classic is wrested from the stillness of reverential exegesis and rigorously returned to the living point of its friction with the present? The Ethics of Potentia takes shape within this question: not as a pacified compendium of interpretations, but as a torsional field, an open threshold traversed by heterogeneous lines that, in Spinoza’s Ethics, find both a center of gravity and a site of collision. The contributions gathered here do not seek to harmonize Spinoza along a monolithic exegetical axis; rather, they endeavor to weave a fabric of differences, diffractions, proximities, and displacements, in which Spinozist concepts are pushed and inflected—without ever being distorted—through dialogue with other interlocutors, disciplines, and urgencies of thought. Originating within the “Laboratory on the Classics” promoted by the MA program in Philosophy at the University of Naples Federico II, the volume unfolds along a double trajectory. On the one hand, it offers a historical-philological and conceptual investigation of Spinoza’s work, developed through rigorous engagements with Descartes, Hobbes, Jacobi, Hegel, and Brentano, and structured around decisive theoretical focus: the mos geometricus as an ethical and political instrument; the single substance; attributes and modes; the three kinds of knowledge; and the conatus as the essence of the singular thing. On the other hand, it tests Spinoza as a reference for contemporary thought, placing him in dialogue with Nietzsche, Deleuze and Guattari, Lacan and Leopardi, as well as with new materialism and eco-cyborg-transfeminist theories. What emerges is a heterogeneous and plural Spinoza, capable of traversing mathematics and ontology, psychoanalysis and phenomenology, literature, perception, and the new materialisms. The themes of potentia as ontological affirmation, liberation from teleology and superstition, desire as the essence of the human, tyranny as a horizontal condition of mind and body, and democracy as the political form of the multitudo constitute the thread that binds the collection together. The volume thus presents itself not as a conclusive synthesis, but as the material trace of a collective experience and, at the same time, of singular expression: a mobile, oscillating composition that, in the genuine spirit of the Ethics, takes the Spinozist text not as an object to be preserved, but as a living dispositif of conceptual and practical transformation.